People's Republic of China-Hong Kong Special Administrative Region : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2019)
This Selected Issues paper discusses income inequality in Hong Kong Special Administrative Region (SAR). Income inequality in Hong Kong SAR remains high, despite declining recently. Redistributive policies implemented by the authorities have helped to lower income inequality. However, inequality is likely to rise in the medium-term due to aging and thus more needs to be done. A package of policies could lower the Gini index by 3-4 points by 2050 including: more progressive salaries tax; higher reliance on recurrent property taxes; and increased public expenditure on social welfare, health, housing, education and childcare. According to recent evidence in the literature, these policies could also boost growth by 0.2-0.5 percentage points per year. Public spending on social welfare could continue to be raised to boost redistribution and increase access of poorer households. Spending on education and childcare should be raised to help lower the market income inequality directly. The commissioned study aiming to determine the demand and supply for childcare services and map out the long-term service development programs, as well as the initiatives mentioned in the 2018 Policy Address, should help in this regard.